Pencapaian Lebar-Pita Antena Mikrostrip dengan Tingkap Tergandeng untuk Frekuensi 2,4 GHz - Ali Hanafiah Rambe; Muhammad Zulfin; Riswan Dinzi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Aperture coupled technique is designed to increase microstrip antenna bandwidth. This paper discusses bandwidth enhancement of the aperture coupled rectangular patch microstrip antenna for working on 2.4 GHz. The optimal design is determined by using the AWR simulator. The fabricated antenna is then analyzed using a vector network analyzer (Anritsu MS2034B). The results show that the antenna is able to achieve 110 MHz bandwidth with return loss is less than –9.54 dB. The bandwidth increment is approximately 77.13% higher than the directly fed antenna.